Social capacity building through applied theatre : developing imagination, emotional and reflective skills in the human services - Yi-Man, Au; O'Toole, John, 1941- (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"As experts in both applied theatre and education, Au Yi-Man and John O'Toole outline how applied theatre techniques can be used to support workers in the human services to develop crucial skills such as resilience, imagination, critical thinking and reflection. Highlighting under-emphasised skills and qualities in the human services professions, this book combines theory with context-specific practice to support capacity-building across sectors. Drawing on a detailed study of NGO workers learning to use applied theatre techniques in professional development, the book offers insight into the learning and experiences of the participants and how these can be applied to future training programs. The book also provides a deeper understanding of how adult learners, from different backgrounds and levels of experience, approach their professional training. Rich with resources, the book features complete course examples, including theatre of the oppressed, process drama, and educational theatre, as core drama techniques. Opening up new opportunities for applied theatre practitioners and educators, this book is a must-read for teachers in any human services field intending to use drama or applied theatre in their training"--
Keywords: Applied theater; Human services personnel -- Training of; Human services -- Study and teaching; DRAMA / General; SOCIAL SCIENCE / Human Services